Pengaruh Waktu Dan Suhu Ekstraksi Daun Melinjo (Gnetum Gnenom L.) terhadap Aktivitas Antioksidan - Susmayanti, Windi; Kusumawati, Dwi Endah (Sultan Agung Islamic University of Semarang, 2023)
Background: The widely cultivated melinjo leaf, or Gentum L genome, is the most valuable commodities cause it contains phenolic chemicals that have antioxidant properties. It is possible to get phenolic chemicals from melinjo leaves by macerating them in ethanol, typically at room temperature. By raising the temperature and length of the extraction process, the yield-maximizing extraction process can be hastened. Methods: The objective of this study is to ascertain the antioxidant activity of melinjo leaves that have been ethanol extracted at 45, 60, and 75 °C. For each temperature change, extraction was done using 96% ethanol (1:10, w/v) for 30 and 45 minutes. The yield, phytochemical assay, total phenolic, and antioxidant activity using the The CUPRAC technique is the variables tested in this study. Results: According to research findings, temperature and extraction time have an impact on yield, content phenolic total, and antioxidant activity. An extract with the maximum antioxidant activity and the consistent phenol content 105.97±5.53 mg GAE/ml and Ic50 of 59.7953 was produced after 45 minutes of extraction at 60°C, but the yield was only 2.22%.